PREVALENCE OF RAMADAN AND FASTING RELATED DIABETICCOMPLICATIONS AMONG DIABETIC PATIENTS - Aisha Noreen et al (Baqai Journal of Health Sciences)
The purpose of this article writing was to go through the prominent changes and associated safety in diabetic patients during the Islamic month of fasting. Various researches have been conducted upon physiological changes in a diabetic patient during the period of Islamic fasting, but still there is no variation perceived pathologically influencing the body weight, blood glucose, HbA1c, insulin, fructose amine, Cpeptide, cholesterol or triglycerides ranges. In the suggestive portion of the following articles, the diabetic patients were advised to carry on with their regular routine. The pre-eminent point noted was that the patients adjusted their drug regimen especially by those with type I diabetes mellitus. Adjusting of drug regimen along with control over the diet and daily activities composed a Ramadan 3D Triangle through which a proper supervision and education came in to being concluding that few of the type I and most of the type II diabetes mellitus patients who wanted to fast could carefully manage it.